The New Nature of Things? Canada's Conservative Government and the Design of the New Environmental Subject - Peyton, Jonathan; Franks, Aaron (Antipode, 2016)
Since coming to power in 2006, Canada's government under Stephen Harper has worked to recalibrate federal regulatory, legislative and economic development frameworks as they overlap in the littoral zone of the environment. We argue that Harper's Conservative government is pursuing a totalizing strategy in reconfiguring the desired Canadian environmental subject. This strategy approaches an integrated design that eclipses the incremental strategic options most Canadian federal governments have understood themselves to be constrained by. This design's basic features include the discursive strategies employed to collapse “the environment” into a singular resource extraction paradigm, a programmatic concentration of power to the executive branch of the Canadian government, and a classical conservative ideology that associates environmental regulation and management with dominion over and improvement of national territory, to the exclusion of other frames and relations. We query the articulation of consent and certainty in relation to the environment and extractive economies in Canada.